Negotiating Customary Practices and Islamic Normativity: A Maqāṣid al-Shariah Analysis of Banten Javanese Marriage Rituals - Finsa Adhi Pratama; Hasniati; Ahmadi; Lincoln James Faikar Mon (Ijtimā'iyya Journal of Muslim Society Research, 2026)
This study analyzes the traditional Banten Javanese marriage rituals as a space through the perspective of Maqāṣid al-Shariah to understand the relationship between local customs and Islamic normativity. The approach used is socio-legal, combining legal analysis with a social perspective, as well as Maqāṣid al-Shariah to evaluate the alignment of customary rituals with the objectives of Islamic law. Data were collected through interviews with religious leaders in Banten and a literature review on traditional marriage and Maqāṣid al-Shariah. Data analysis utilized a qualitative descriptive method with stages of data reduction, data presentation, and conclusion drawing. The findings show that the traditional Banten Javanese marriage rituals, such as nakoni, mastikaken, seserahan, maca syaikh, akad nikah, sungkeman, yalil, saweran, tarik bakakak, marhaban, and ngalih turu, contain Islamic values such as deliberation, prayer, respect for parents, consent of the bride and groom, social solidarity, and strengthening family ties. However, some customary practices may potentially become a social-economic burden or be understood in a magical context, which risks contradicting Islamic principles. From the Maqāṣid al-Shariah perspective, these rituals are acceptable as long as they preserve religion, life, intellect, offspring, and wealth, and do not conflict with the principles of tawhid, rationality, justice, and simplicity. This study provides an understanding of traditional rituals in alignment with Maqāṣid al-Shariah principles and emphasizes the importance of reconstructing the understanding of customs to ensure that marriage traditions remain preserved as a cultural identity while being in harmony with Islamic principles and social welfare.